Elevating Instruction: Enhancing Literacy Practices for Advanced Readers in Primary Grades. Issue 1 (January 2020) - Kreamer, H. Michelle; Orme, Sarah; Hobson, Victoria; Moran, Melinda; Mahoney, Kerrigan; Moon, Tonya R.; Brighton, Catherine
The tool, Elevating Instruction: A Planning Tool, was designed to aid teachers in improving literacy instruction to best meet the academic needs of all students, including advanced readers in the primary classroom. It is crucial for teachers to elevate reading practices for advanced readers during the time when young learners are developing skills to be lifelong readers. Teachers can do this by promoting authentic choice, encouraging student agency and ownership, supporting meaningful peer interactions, and collecting and using formative data. To this end, the authors address these four instructional components within the scope of a literacy block in an elementary classroom using an easy-to-access and easy-to-implement planning tool, which teachers can use to enhance instruction for all students. The use of this tool is depicted by a classroom teacher working with a gifted resource teacher (GRT), demonstrating how the tool can be used to support teachers as they work to improve and elevate literacy instruction.